The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1051/0004-6361/201936743
|View full text |Cite
|
Sign up to set email alerts
|

The young massive SMC cluster NGC 330 seen by MUSE

Abstract: Context. A majority of massive stars are part of binary systems, a large fraction of which will inevitably interact during their lives. Binary-interaction products (BiPs), i.e. stars affected by such interaction, are expected to be commonly present in stellar populations. BiPs are thus a crucial ingredient in the understanding of stellar evolution. Aims. We aim to identify and characterize a statistically significant sample of BiPs by studying clusters of 10 − 40 Myr, an age at which binary population models p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 123 publications
4
27
1
Order By: Relevance
“…3), as Be stars (Pols et al 1991). Recent photometric and spectroscopic results show that a significant fraction of the MS stars in young clusters ( ∼ < 100 Myr) within two to three magnitudes below the turnoff are Be stars (Milone et al 2018;Bodensteiner et al 2019). As demonstrated by our animation (Fig.…”
Section: Comparison To Observed Star Clusterssupporting
confidence: 76%
See 1 more Smart Citation
“…3), as Be stars (Pols et al 1991). Recent photometric and spectroscopic results show that a significant fraction of the MS stars in young clusters ( ∼ < 100 Myr) within two to three magnitudes below the turnoff are Be stars (Milone et al 2018;Bodensteiner et al 2019). As demonstrated by our animation (Fig.…”
Section: Comparison To Observed Star Clusterssupporting
confidence: 76%
“…Recently, photometric studies using the Hubble Space Telescope revealed that the MS of young and intermediate age star clusters (14-600 Myr) in the Magellanic Clouds and in the Galaxy is split into two distinct MSs, as well as an extended MS turnoff region (D'Antona et al 2017;Milone et al 2018;Li et al 2019, and references therein). Furthermore, the young clusters show distinct groups of emission-line stars, extending more than two magnitudes below the turnoff (Milone et al 2018), most of which are spectroscopically identified as Be stars (Bodensteiner et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is not completely implausible: If Be stars owe their rapid rotation to spin-up by mass overflow from a now underluminous companion (e.g., Langer et al 2020a, and references therein) a resulting rejuvenation of the outer Be star is one possible explanation. Some blue stragglers in open clusters have been reported to show Hα in emission and may be classical Be stars (Aidelman et al 2018;Bodensteiner et al 2020).…”
Section: )mentioning
confidence: 99%
“…The first surveys of the massive star populations in nearby galaxies have already started with MUSE. Demonstrations were made for dense star clusters in the LMC (Castro et al 2018(Castro et al , 2021 and SMC (Bodensteiner et al 2020), and for wider fields in the Sculptor Group galaxies NGC 300 (Roth et al 2018, henceforth Paper I) and NGC7793 (Wofford et al 2020).…”
Section: Introductionmentioning
confidence: 99%